Primary care teams’ experiences of delivering mental health care during the COVID-19 pandemic: a qualitative study - Ashcroft, Rachelle; Donnelly, Catherine; Dancey, Maya; Gill, Sandeep; Lam, Simon; Kourgiantakis, Toula; Adamson, Keith; Verrilli, David; Dolovich, Lisa; Kirvan, Anne; Mehta, Kavita; Sur, Deepy; et al. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Integrated primary care teams are ideally positioned to support the mental health care needs arising during the COVID-19 pandemic. Understanding how COVID-19 has affected mental health care delivery within primary care settings will be critical to inform future policy and practice decisions during the later phases of the pandemic and beyond. The objective of our study was to describe the impact of the COVID-19 pandemic on primary care teams’ delivery of mental health care. Methods A qualitative study using focus groups conducted with primary care teams in Ontario, Canada. Focus group data was analysed using thematic analysis. Results We conducted 11 focus groups with 10 primary care teams and a total of 48 participants. With respect to the impact of the COVID-19 pandemic on mental health care in primary care teams, we identified three key themes: i) the high demand for mental health care, ii) the rapid transformation to virtual care, and iii) the impact on providers. Conclusions From the outset of the COVID-19 pandemic, primary care quickly responded to the rising mental health care demands of their patients. Despite the numerous challenges they faced with the rapid transition to virtual care, primary care teams have persevered. It is essential that policy and decision-makers take note of the toll that these demands have placed on providers. There is an immediate need to enhance primary care’s capacity for mental health care for the duration of the pandemic and beyond.